Kontribusi Pemuda terhadap Upaya Pelestarian Penyu: Analisis Partisipasi di Desa Wiring Tasi, Kabupaten Pinrang - Ismail, Muh.; Jufri, Muhammad (Kolaborasi Masyarakat, 2026)
Sea turtles are endangered marine species facing increasing anthropogenic pressures in coastal areas, highlighting the need for local community involvement, particularly among young people, in conservation efforts. This study aims to analyze the forms of youth participation as well as the supporting and inhibiting factors influencing their involvement in sea turtle conservation at Lowita Beach, Wiring Tasi Village, Pinrang Regency. The study employed a descriptive qualitative approach, with data collected through field observations, semi-structured interviews, and document analysis involving six key informants directly engaged in conservation activities. Data were analyzed using thematic analysis. The results indicate that youth participation is manifested through contributions of ideas, labor, skills, provision of supporting facilities, and self-funded financial support. Such participation is supported by community environmental awareness, the presence of youth communities as collective platforms, and moral support from the village government. However, youth participation continues to face constraints, including limited resources, low motivation among some youth, coastal environmental pollution, and illegal sea turtle hunting practices. Theoretically, these findings underscore the role of youth as agents of change in community-based conservation. Practically, the study recommends strengthening institutional and policy support for youth communities to ensure the sustainability of sea turtle conservation in coastal areas.